Effectiveness of WhatsApp Messages Regarding Improved Agricultural Production Technology - Patel, Neerja; Dixit, A.K.; Singh, S.R.K. (Indian Journal of Extension Education, 2020)
Agricultural information can play very important role in the development of small farmers. By using communication technologies farmers can increase their production and income. In the perspective of the mobile phones farmers can directly communicate with buyers and customers for selling their produce at good price. In remote areas farmers are still facing many problems in using technologies due to lack of infrastructure and awareness. Most of the farmers still depend on old traditional methods in agriculture due to lack of knowledge, illiteracy and trainings. WhatsApp technology has provided a platform for farmers to share their knowledge and information among each other on crucial time for market rates and weather information. WhatsApp messenger is a proprietary, cross platform instant messaging application for smart phones. In addition to text messaging, users can send images, video, and audio media messages. The study conducted in Dewas district showed that the WhatsApp was able to increase the knowledge of the farmers on soybean production technology and was farmers were at high to low level of knowledge regarding social media based technical information.
Keywords: Effectiveness; Knowledge; Social media